Quantitative Analysis of Mutant Subclones in Chronic Myeloid Leukemia: Comparison of Different Methodological Approaches - Preuner, Sandra; Barna, Agnes; Frommlet, Florian; Czurda, Stefan; Konstantin, Byrgazov; Alikian, Mary; Machova Polakova, Katerina; Sacha, Tomasz; Richter, Johan; Lion, Thomas; Gabriel, Christian (International journal of molecular sciences, 2016)
Identification and quantitative monitoring of mutant BCR-ABL1 subclones displaying resistance to tyrosine kinase inhibitors (TKIs) have become important tasks in patients with Ph-positive leukemias. Different technologies have been established for patient screening. Various next-generation sequencing (NGS) platforms facilitating sensitive detection and quantitative monitoring of mutations in the ABL1-kinase domain (KD) have been introduced recently, and are expected to become the preferred technology in the future. However, broad clinical implementation of NGS methods has been hampered by the limited accessibility at different centers and the current costs of analysis which may not be regarded as readily affordable for routine diagnostic monitoring. It is therefore of interest to determine whether NGS platforms can be adequately substituted by other methodological approaches. We have tested three different techniques including pyrosequencing, LD (ligation-dependent)-PCR and NGS in a series of peripheral blood specimens from chronic myeloid leukemia (CML) patients carrying single or multiple mutations in the BCR-ABL1 KD. The proliferation kinetics of mutant subclones in serial specimens obtained during the course of TKI-treatment revealed similar profiles via all technical approaches, but individual specimens showed statistically significant differences between NGS and the other methods tested. The observations indicate that different approaches to detection and quantification of mutant subclones may be applicable for the monitoring of clonal kinetics, but careful calibration of each method is required for accurate size assessment of mutant subclones at individual time points.
Keywords: Polymerase Chain Reaction; vysoce účinné nukleotidové sekvenování; Sequence Analysis, DNA; DNA; High-Throughput Nucleotide Sequencing; sekvenční analýza DNA; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Comparative Genomic Hybridization; lidé; chronická myeloidní leukemie; srovnávací genomová hybridizace; bcr-abl fúzní proteiny; Fusion Proteins, bcr-abl; polymerázová řetězová reakce